2021
DOI: 10.1371/journal.pone.0253938
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of financial self-control strategies: Comparing empirical findings with online media and lay person perspectives on what helps individuals curb spending and start saving

Abstract: Self-control can be assisted by using self-control strategies rather than relying solely on willpower to resist tempting situations and to make more goal-consistent decisions. To understand how self-control strategies can aid financial goals, we conducted a meta-analysis (Study 1) to aggregate the latest research on self-control strategies in the financial domain and to estimate their overall effectiveness for saving and spending outcomes. Across 29 studies and 12 different self-control strategies, strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 91 publications
(136 reference statements)
0
11
0
Order By: Relevance
“…Their results showed that although almost all experts opposed this event, many web-based posts supported it. To understand how self-control strategies helped reach financial goals, Davydenko et al ( 47 ) conducted a meta-analysis to aggregate the latest research on self-control strategies in the financial domain and estimate their overall effectiveness for saving and spending outcomes. Their studies highlighted the academic, online media, and lay-person perspectives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their results showed that although almost all experts opposed this event, many web-based posts supported it. To understand how self-control strategies helped reach financial goals, Davydenko et al ( 47 ) conducted a meta-analysis to aggregate the latest research on self-control strategies in the financial domain and estimate their overall effectiveness for saving and spending outcomes. Their studies highlighted the academic, online media, and lay-person perspectives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…How much does media advice overlap with self‐regulation theories and financial decisions research? A coding analyses of a sample of online media articles on saving and spending advice (Davydenko et al., 2021) found that about half of media recommended financial self‐regulation strategies were similar to strategies studied in the academic literature—and about half were different. For example, strategies recommended in the media that reflect academic knowledge were the automatization of savings (Bronchetti et al., 2011; Rabinovich & Webley, 2007) and planning ahead by making shopping lists (e.g., Gilbert et al., 2002).…”
Section: Financial Decisions and Financial Self‐regulationmentioning
confidence: 99%
“…For example, strategies recommended in the media that reflect academic knowledge were the automatization of savings (Bronchetti et al., 2011; Rabinovich & Webley, 2007) and planning ahead by making shopping lists (e.g., Gilbert et al., 2002). A sample of lay people reporting their own everyday strategy use also reported financial self‐regulation strategies with limited overlap with the academic literature (Davydenko et al., 2021). Table 1 presents quotes from participants who report their own personal financial strategies (Peetz & Davydenko, 2021).…”
Section: Financial Decisions and Financial Self‐regulationmentioning
confidence: 99%
See 2 more Smart Citations